Analisis Kualitas Layanan Website Pemerintahan Dispusip Kota Pekanbaru Dengan Metode E-Govqual - Darmawan, Reza; Salisah, Febi Nur; Anggraini, A; Anwar, Tengku Khairil (STIKOM Tunas Bangsa Pematangsiantar, 2023)
The Pekanbaru City Office is a library in the field of information media dissemination using an E-Government-based website. This study aims to determine the results of service quality analysis on the Pekanbaru City Disputation website using the E-Govqual method which functions to measure the quality of E-Government services with 4 E-Govqual dimensions consisting of, ease of use, trust. , content and appearance of information, and citizen support. In interviews with 30 users, it was found that there were several problems regarding the website. By using E-Govqual the measurement of the information system will provide dimensions that are in accordance with the problem variables taken from interviews with these users. This study collected data with a questionnaire as a research instrument. The research questionnaire consisted of 24 statements with a total of 100 respondents. The results of this analysis conclude that there are 4 variables that are the top priority for improving the quality of website services, namely search (EF3), use of personal data (TR4), images, colors, graphics, animation and web size (CA1), and frequent questions filed (CS6). There are also 4 variables that have the highest satisfaction score that need to be maintained, namely the website address/url (EF2), access control (TR2), completeness of information (CA5), and knowledge and courtesy of employees (CS4). From the results obtained the average value of statistical analysis exceeds 3 of the four dimensions, this shows the need to improve website performance and the citizen support variable has the highest significant influence on community support on the Pekanbaru City Dispusip website.